Stres pengangkutan pada ternak unggas, pengaruh dan upaya penanggulangan - Mohammad Hasil Tamzil; Budi Indarsih; I Nyoman Sukartha Jaya; Ni Ketut Dewi Haryani (Universitas Sebelas Maret, 2022)
The transportation of poultry from the farmer to the chicken slaughterhouse (CSH) or to the chicken slaughterplace (CSP) is a chain that plays a significant role in determining the quality of poultry meat. During the transportation, the birds experienced stress from the process of moving from cages to boxes, overcrowding of chickens in boxes, unavailability of feed and drinking water, stress of heat and wind, the process of moving chickens from boxes to temporary shelters, as well as fatigue and fear. All of these processes act simultaneously as stressors, so that chickens suffer from acute stress. Stress in livestock has an impact on the emergence of glycolytic processes, glycolysis and ATP hydrolysis. Muscle glycogen will undergo enzymatic glycolysis and produce lactic acid which triggers changes in the pH of the meat so that the meat becomes pale, soft and watery (PSE = pale, soft, exudative). The most detrimental impact is the emergence of a high mortality rate, so this transportation process must be handled carefully. Some things can be done to reduce the stress of transportation include: chickens that are transported in good health, before transportation, supplymenting antistress is offered, prior to leaving the chickens are sprayed with water. Catching the birds is avoided, and put them in the box and then remove from the box gently. Filling boxes must be in accordance with standards, and transportation is carried out at night.